Synthesis and Investigation of Antimicrobial and Antioxidant Activity of 3-Nitro-N- (3-chloro-2-oxo-substituted-phenyl-azetidin-1-yl)naphtho [2,1-b]furan-2-carboxamides - K. Shashikala Devi; M. Ramaiah; D. L. Roopa; V. P. Vaidya (E-Journal of Chemistry)
Ethyl-3-nitronaphtho[2,1-b]furan-2-carboxylate (2) has been synthesized from ethyl naphtha [2,1-b]furan-2-carboxylate (1). This nitro product on reaction with hydrazine hydrate formed 3-nitronaphtho [2,1-b] furan-2-carbohydrazide (3). Various Schiff bases 3-nitro-N1(aryl-methylene)-substituted-naphtho [2,1-b]furan-2-carbohydrazides 4(a-g) were obtained by treating hydrazide (3) with different aldehydes. These Schiff bases on reaction with chloro acetyl chloride in presence of triethylamine in dioxane yielded 3-nitro-N-(3-chloro-2-oxo-substituted-phenyl-azetidine-1-yl) naphtha [2,1-b]furan-2-carboxamides 5(a-g). All the newly synthesized compounds have been characterized by spectral and analytical studies. The Schiff bases, 4a-g and azetidione derivatives, 5a-g have been studied for antioxidant and antimicrobial activities.